Enhanced soluble sugar content in tomato fruit using CRISPR/Cas9-mediated SlINVINH1 and SlVPE5 gene editing - Baike Wang (PeerJ Inc., 2021)
Soluble sugar is known to improve the sweetness and increase tomato sauce yield. Studies have focused on improving the content of soluble sugar in tomato fruits, usually by promoting functional genes. We studied two genes (SlINVINH1 and SlVPE5) that inhibited the accumulation of soluble sugar in tomato fruits and obtained two genes’ knocked-out lines (CRISPR-invinh1 or CRISPR-vpe5) using CRISPR/Cas9. Aggregated lines with CRISPR-invinh1 and CRISPR-vpe5 were gained by hybridization and self-pollination. Compared to wild-type lines, the glucose, fructose, and total soluble solid (TSS) contents of CRISPR-invinh1 and CRISPR-vpe5 increased significantly. Glucose, fructose, and TSS levels further improved simultaneously with CRISPR-invinh1 and CRISPR-vpe5 than with single gene knock-out lines. This indicates that these genes have a synergistic effect and will increase the soluble sugar content. Thus, the knock-out SlINVINH1 and SlVPE5 may provide a practical basis for improving the sweetness of tomato fruits and their processing quality.